Maxillary Sinus Mucocele As an Unusual Complication of Orthognathic Surgery: Case Report - Ahmet Emin Demirbaş; Cihan Topan; Gökhan Yılmaz; Alper Alkan (Selcuk Dental Journal)
Mucoceles of the paranasal sinuses are benign cystic formations lined by epithelium which show local enlargement with mucus collection. These lesions are usually seen in the frontal sinus, rarely in the ethmoid and maxillary sinus. It is believed to develop after the obstruction of the sinus ostium due to chronic sinusitis, polyps, bone tumours, previous trauma and allergic rhinitis. Maxillary sinus mucoceles are rarely seen after surgical operations and has harmful effects on neighboring structures. In this case report, we present a maxillary sinus mucocele which was developed after orthognathic surgery with its surgical treatment and postoperative follow-up.Keywords: Maxillary sinus mucocele; orthognathic surgery; ostium.